2012
DOI: 10.1007/s00737-012-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

A latent modeling approach to genotype–phenotype relationships: maternal problem behavior clusters, prenatal smoking, and MAOA genotype

Abstract: This study illustrates the application of a latent modeling approach to genotype–phenotype relationships and gene×environment interactions, using a novel, multidimensional model of adult female problem behavior, including maternal prenatal smoking. The gene of interest is the mono-amine oxidase A (MAOA) gene which has been well studied in relation to antisocial behavior. Participants were adult women (N=192) who were sampled from a prospective pregnancy cohort of non-Hispanic, white individuals recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…Here, we used the dominant, recessive and codominant models to analyze the data. The OR of active group vs. inactive group was calculated in MOA-A VNTR, based on alleles with 3.5 or four repeats with greater efficiency than other alleles (Lewis et al, 2007;McGrath et al, 2012). The recessive model was applied in MAO-B for the consistent results in published articles.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used the dominant, recessive and codominant models to analyze the data. The OR of active group vs. inactive group was calculated in MOA-A VNTR, based on alleles with 3.5 or four repeats with greater efficiency than other alleles (Lewis et al, 2007;McGrath et al, 2012). The recessive model was applied in MAO-B for the consistent results in published articles.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies with high quality exposure measurement have demonstrated links to disruptive behavior, deficits in executive function, and alterations in orbital frontal brain regions that subserve reward processing (Ernst, Moolchan, & Robinson, 2001; Lotfipour, et al, 2009; Wakschlag, et al, 2002). Gene×environment interactions have also been demonstrated, including the interaction of prenatal tobacco exposure with a functional polymorphism in the monoamine oxidase A gene ( MAOA ) that increases susceptibility to environmental adversity (Kim-Cohen et al 2006; Wakschlag et al 2009; McGrath et al 2012). Adoption studies, which are designed to disentangle heritability from postnatal influences (Leve et al, 2013), have further demonstrated independent effects of MDSP on child externalizing problems in exposed children reared by genetically unrelated adoptive parents (Marceau et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The few existing studies that have specifically compared smokers who quit early in pregnancy (pregnancy quitters) with smokers who continued smoking during pregnancy (persistent pregnancy smokers) have shown significant differences in history of antisocial behavior between these groups (Wakschlag, Pickett, Middlekamp et al, 2003; Kodl & Wakschlag, 2004; Pickett, Wilkinson, & Wakschlag, 2009; McGrath et al, 2012). Importantly, while never smokers may differ from ever smokers, pregnancy quitters are also significantly different from persistent pregnancy smokers (Massey, Bublitz, Magee, et al, 2015, Massey, Estabrook, O’Brien et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We also take a spectrum approach to externalizing behavior, which enhances linkage to mechanisms, has ecological validity, and yields a highly heritable component of behavior (Farmer et al, 2009; Krueger et al, 2002; 2007). We have found that this approach captures phenotypic patterns well (McGrath et al, 2012). While our sample is fairly small relative to many G × E studies, this limitation is partially offset by the high quality measurement of exposure (prospective, repeated measure and includes biologic measures) and of externalizing behavior (multi-faceted, repeated-measures) and rigorous control for gene-environment correlation (r ge ).…”
Section: Introductionmentioning
confidence: 85%